The Role Of Steam Pedagogy In The Formation Of Environmental Competence Among Primary School Teachers (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article discusses the formation of interdisciplinary ecological culture through environmental education for students, STEAM education, interdisciplinary collaboration, the manifestation of creative abilities, and extracurricular independent learning.